RATIONALE OF CONSTRUCTION OF HYDRO-SPRAYING INSTALLATION OF TUNNEL TYPE - Арендаренко, В. М.; Харак Р. М., Р. М.; Самойленко, Т. В. (Scientific Progress & Innovations, 2013)
Functional diagram of hydro-spraying installation of tunnel type was substantiated. The benefits of this installation in the process of collecting and destroying the Colorado potato beetle were given. The necessity of introducing the functional scheme of the jet pump for pumping the working fluid of the trays tunnel chambers was substantiated. Research has found that increasing of the speed of the working fluid at the outlet of the nozzle jet pump depends on the ratio of input and output nozzle diameter. Using the equation of conservation of the fixed costs of working fluid, exit velocity of the working fluid from the nozzle of the jet pump hydro-spraying installation is theoretically grounded.